Strength control of the hood of diesel electric locomotive - Tomek, Petr; Středová, Doubravka (Univerzita Pardubice, 2013)
This article presents two methods for evaluating strength of hood railway locomotives. The hood is subject to the standards for railway applications ČSN EN 12663-1 [1]. The first method is anchored in the standard for rail applications ČSN EN 12663-1 [1]. This method is based on the principle of evaluation of the pseudo-elastic stress. The second method uses the results of nonlinear numerical analyzes GMNA. The second method is based on the knowledge of modern science and technology. Structural strength is then evaluated from the real limit state. The results in this article are used for the structural design modifications to the existing hood.
Kontrola pevnosti kapoty diesel elektrické lokomotivy
Nachkritisches verhaltung die zylindrische schale